2016
DOI: 10.5916/jkosme.2016.40.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Latest welding technology for storage and transportation facilities of liquified natural gas

Abstract: The need for storage and transportation facilities of liquefied natural gas have increased significantly because of global environmental regulations and recent shale gas innovation in North America. There is severe competition between Korea, Japan, and China for receiving manufacturing orders of LNG carriers or LNG storage tanks. Rationalization of the welding process used in the manufacturing of LNG facilities plays an important role in the above competition. This review paper presents the current global stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Lee [ 9 ] researched the welding problem by the magnetization of 9% nickel steel. Kim [ 10 ] found that GMAW (gas metal arc welding) of 9% nickel steel improved the high temperature cracking susceptibility, but had a bad effect on the strength of the welded area. Saitoh [ 11 ] developed a high nickel-based steel with good toughness for cryogenic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lee [ 9 ] researched the welding problem by the magnetization of 9% nickel steel. Kim [ 10 ] found that GMAW (gas metal arc welding) of 9% nickel steel improved the high temperature cracking susceptibility, but had a bad effect on the strength of the welded area. Saitoh [ 11 ] developed a high nickel-based steel with good toughness for cryogenic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lee [ 8 ] explains the problem of the welding part caused by the magnetization of 9% nickel steel, and predicts that the utilization of 9% nickel steel will increase through automation and overcoming the problem of the future welding process. Kim [ 9 ] et al reported that, when 9% nickel steel was welded by GMAW (gas metal arc welding), the high-temperature cracking susceptibility was good, but when the amount of heat input was increased, the strength of the welded portion decreased. When looking at the current status of research on the design and mechanical properties of cryogenic steel and A553-1 steel used to manufacture LNG storage tanks, Saitoh et al [ 10 ] developed a high Ni-based 9% Ni steel with excellent low-temperature toughness to ensure safety with LNG storage tanks.…”
Section: Introductionmentioning
confidence: 99%